2017
DOI: 10.1167/17.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotopic updating of visual feature information

Abstract: Saccades shift the retina with high-speed motion. In order to compensate for the sudden displacement, the visuomotor system needs to combine saccade-related information and visual metrics. Many neurons in oculomotor but also in visual areas shift their receptive field shortly before the execution of a saccade (Duhamel, Colby, & Goldberg, 1992; Nakamura & Colby, 2002). These shifts supposedly enable the binding of information from before and after the saccade. It is a matter of current debate whether these shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…Although predictive remapping has been widely studied, there is an ongoing debate regarding whether and how feature information of visual objects is remapped during this process (Cavanagh, Hunt, Afraz, & Rolfs, 2010;Ezzati, Golzar, & Afraz, 2008;Harrison, Retell, Remington, & Mattingley, 2013;He, Mo, & Fang, 2017;Lescroart, Kanwisher, & Golomb, 2016;Mayo & Sommer, 2010;Melcher, 2005Melcher, , 2007Melcher, , 2010Pelli & Cavanagh, 2013;Zimmermann, Weidner, & Fink, 2017;). On the one hand, several psychophysical studies have suggested that visual feature information, such as orientation and letter information, is transmitted around the time of a saccade (Harrison et al, 2013;He et al, 2017;Melcher, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One source of visual stability may be the integration of preand post-saccadic visual information (Helmholtz, 1867;Melcher, 2011;Wurtz, 2008). Recent gaze-contingent experimental designs have revealed that orientation (Ganmor et al, 2015;Wolf and Schütz, 2015;Zimmermann et al, 2017), object size (Valsecchi and Gegenfurtner, 2016), visual motion (Fabius et al, 2016), and even whole-object information (Castelhano and Pereira, 2017;Schut et al, 2016) are integrated across saccades in a statistically optimal fashion that takes into account the relative reliability of pre-saccadic and post-saccadic input (Ganmor et al, 2015;Herwig, 2015;Wolf and Schütz, 2015). Nonetheless, the time-course of trans-saccadic perception and, in particular, the content of perception immediately after fixation-onset remain controversial (for review, Melcher and Morrone, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One source of visual stability may be the integration of pre- and post-saccadic visual information (Helmholtz, 1867; Melcher, 2011; Wurtz, 2008). Recent gaze-contingent experimental designs have revealed that orientation (Ganmor et al, 2015; Wolf and Schütz, 2015; Zimmermann et al, 2017), object size (Valsecchi and Gegenfurtner, 2016), visual motion (Fabius et al, 2016), and whole-object information (Castelhano and Pereira, 2017; Schut et al, 2016) are integrated across saccades in a statistically optimal fashion taking into account the relative reliability of pre-saccadic and post-saccadic input (Ganmor et al, 2015; Herwig, 2015; Wolf and Schütz, 2015). Nonetheless, the time-course of trans-saccadic perception and, in particular, the content of perception immediately after fixation-onset remain controversial (for review, Melcher and Morrone, 2015)…”
Section: Introductionmentioning
confidence: 99%